Pengaruh Literasi Keuangan dan Financial Self-Efficacy terhadap Risk Credit Behavior dalam Penggunaan Shopee PayLater pada Pengguna Usia 18-25 Tahun (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of financial literacy and financial self-efficacy on risky credit behavior among Shopee PayLater users aged 18–25 years. The research employed a quantitative approach using a purposive sampling method, involving 101 respondents. The research instrument consisted of a closed-ended questionnaire utilizing a Likert scale, while data analysis was conducted through descriptive analysis, classical assumption tests, multiple linear regression analysis, t-test, and F-test with the assistance of SPSS version 25. The results reveal that, partially, financial literacy does not have a significant influence on risky credit behavior, whereas financial self-efficacy has a significant impact. Simultaneously, both variables significantly affect risky credit behavior, although their combined contribution to the variance in risky credit behavior is only 9.6%. These findings emphasize the importance of financial education programs that not only focus on enhancing financial literacy but also on strengthening individual confidence in financial management in order to foster healthier credit behavior among young generations